2005
DOI: 10.1007/s10565-005-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced in heart and other tissues by rat dermal exposure to JP-8 fuel

Abstract: Limited information is available regarding the development of systemic organ stress by dermal exposure to JP-8 fuel. In this study, the systemic stress potential of this fuel is evaluated in a rat model subjected to dermal applications of JP-8 for 7 days at 300 microl per day. Tissue histology indicated that JP-8 induces morphological alterations that suggest that tissue stress in the heart is more substantial than stress in the kidney and liver. Immunoblot analysis of tissues revealed increased levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The published data have demonstrated the formation of reactive oxygen species (ROS) during JP-8 treatment (Boulares et al 2002). Cell culture models have showed that JP-8 can induce a range of molecular responses including cytotoxicity, cytokine release, DNA damage, oxidative stress (OS), and apoptosis (Larabee et al 2005;Cavallo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The published data have demonstrated the formation of reactive oxygen species (ROS) during JP-8 treatment (Boulares et al 2002). Cell culture models have showed that JP-8 can induce a range of molecular responses including cytotoxicity, cytokine release, DNA damage, oxidative stress (OS), and apoptosis (Larabee et al 2005;Cavallo et al 2006).…”
Section: Introductionmentioning
confidence: 99%